The complete ElfQuest. Volume six - Pini, Wendy; Pini, Wendy; Pini, Richard; Marx, Christy; Strait, Sonny (Dark Horse Books, 2019)
"This new treasury of the classic fantasy series by Wendy and Richard Pini collects deeper cuts of canonical backstories and Wolfrider essentials. Discover how humans, looking to escape their own barren lands, invade Bearclaw's forest and cause unseen disaster for the elves. Also collected are stories showcasing the deep bond of brotherhood between Cutter and Skywise. Whether hatching a plan to steal treasure from the Troll King, or dealing with magical madness that reverts one of them to feral wolf-mind, adventure is never far away from these two!"--Provided by publisher